MOBILE APPLICATION M-WARTA PADA USER READING DENGAN MULTI CLIENT SERVER BERBASIS ANDROID - Agung Ferry Anggara; M Ghofar Rohman; Nurul Fuad (Universitas Islam Lamongan, 2017)
News is a primary thing in the daily life of a person because human life definitely requires an information. That information can be about jobs, education, and so forth. With news, someone knows something new, without news, a person can be said as a frog in a shell. One can access the news through various media, those are; print media, electronic media, and internet media. Most people want news that can be accessed anywhere and anytime. Thus the M-News application can make a news becomes portable news and how news writers can immediately provide a message at that time. The system of this application is client serverfor the news writers and readers that can give and receive the latest information. The main target of this news service users are mobile users such as mobile phones. Android is a smartphone operating system that is being developed at this time. Android has many advantages over other operating systems. Among others, the operating system can be changed in accordance with the users’ needs and there are many computer applications available for Android smartphones. Therefore, Android is currently becoming the most enthused technology nowadays. Android application used to help the news writers to deliver the news and the news anchors to receive the latest news.